Priming VRC01-precursor B cells with non-envelope immunogens disfavors boosting with HIV-1 envelope - Andrew Wilcox-King; Yu-Hsin Wan; Samuel C. Scharffenberger; Crystal B. Chhan; Amelia R. Davis; Leah J. Homad; Emilie Seydoux; Kellie J. MacPhee; Latha Kallur Siddaramaiah; Mariane Melo; Pia Dosenovic; Darrell J. Irvine; et al. (npj Vaccines)
Abstract VRC01-class antibodies are a genetically restricted class of antibodies capable of potently neutralizing diverse strains of HIV-1. Unmutated VRC01 precursors fail to recognize recombinant HIV-1 Envelope (Env) proteins, which necessitated the development of germline targeting vaccine immunogens capable of initiating VRC01-class B cell response. Among these, we developed an anti-idiotypic monoclonal antibody (ai-mAb)-derived VRC01 class targeting immunogen. Because it is distinct from Env, we speculated that the ai-mAb will selectively engage naive VRC01 class B cells while limiting B cell responses directed at off-target epitopes on Env during prime-boost regimens. Here, we evaluated the serum and B cell responses to ai-mAb prime/Env boost, and Env-prime/Env boost regimens in a murine adoptive transfer model where VRC01 precursor B cells are present at physiological levels. We found that the Env-Env regimen led to the greatest expansion of on-target VRC01 B cells, drove larger VRC01-class GC responses, and elicited higher titers of circulating antibodies despite also eliciting substantial off-target Env-specific responses. Single-cell sorting experiments revealed that the ai-mAb was driving off-track somatic mutations. IgG transfer experiments demonstrated that circulating off-target antibodies provide a positive feedback mechanism that potentiates on-target B cell responses. Collectively, the results suggest that non-Env immunogens are not ideal for priming VRC01-class B cells, where sequential boosting with Env will be required to drive maturation of neutralizing breadth.